1990
DOI: 10.1200/jco.1990.8.2.280
|View full text |Cite
|
Sign up to set email alerts
|

Invasive fungal disease in pediatric acute leukemia patients with fever and neutropenia during induction chemotherapy: a multivariate analysis of risk factors.

Abstract: We evaluated the courses of 115 consecutive cases of pediatric acute leukemia treated with induction chemotherapy. Seventy-two patients developed fever associated with neutropenia; 15 developed systemic fungal infections. We reviewed multiple demographic and treatment characteristics of these patients in an attempt to identify potential risk factors for the development of invasive fungal disease (IFD). Risk factors identified in a univariate analysis included duration of neutropenia after first fever (P less t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
48
2
2

Year Published

1993
1993
2017
2017

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 110 publications
(54 citation statements)
references
References 0 publications
2
48
2
2
Order By: Relevance
“…The real-time PCR assay provides a high sensitivity and specificity for the detection of fungal DNA and rapidly identifies most of clinically relevant Aspergillus species (20). Many studies have reported the correlation between the presence of proven, probable, and possible criteria of IFIs according to the EORTC-MSG criteria and PCR results of the respective patients' sera (17,21,22). The results of the present study show 5/8 patients with proven and 5/6 patients with probable criteria.…”
Section: Discussionsupporting
confidence: 53%
“…The real-time PCR assay provides a high sensitivity and specificity for the detection of fungal DNA and rapidly identifies most of clinically relevant Aspergillus species (20). Many studies have reported the correlation between the presence of proven, probable, and possible criteria of IFIs according to the EORTC-MSG criteria and PCR results of the respective patients' sera (17,21,22). The results of the present study show 5/8 patients with proven and 5/6 patients with probable criteria.…”
Section: Discussionsupporting
confidence: 53%
“…are carried as commensals into hospital settings by patients, health care workers, and visitors. Particular groups of patients in intensive care units are at risk, especially bone marrow transplant recipients and other groups of immunosuppressed patients (24,47,154,165,302,402,414,421). Surveillance studies indicate that the frequency of BSI and other forms of invasive candidiasis acquired in hospital settings continues to increase (24,264).…”
Section: Determining the Origin Of Nosocomial Infectionsmentioning
confidence: 99%
“…Several Candida species are pervasive pathogens capable of causing systemic infection in critically ill and severely immunocompromised patients [1][2][3][4]. In the 1980s, Candida species were reported to be the seventh most common nosocomial pathogens hospitalwide, ranking fourth in intensive care units (ICUs) where they accounted for c. 10% of all bloodstream infections [5][6][7].…”
Section: Introductionmentioning
confidence: 99%